2019
DOI: 10.1002/ajp.23059
|View full text |Cite
|
Sign up to set email alerts
|

Ecological fragmentation effects in mouse lemurs and small mammals in northwestern Madagascar

Abstract: Habitat loss and fragmentation are major ecological forces threatening animal communities across the globe. These issues are especially true in Madagascar, where forest loss is ongoing. We examined the effects of forest fragmentation on the distribution and abundance of sympatric, endemic gray, and golden-brown mouse lemurs (Microcebus murinus and Microcebus ravelobensis), the endemic western tufttailed rat (Eliurus myoxinus), and the invasive black rat (Rattus rattus) in two regions in northwestern Madagascar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 56 publications
(87 reference statements)
3
53
1
Order By: Relevance
“…A high ecological flexibility of this lemur species towards variable ecological conditions at forest edges may explain such seemingly contradictory responses, and also its occurrence in several different types of microhabitats [36]. Such a flexibility may enable this species to cope with disturbances and some anthropogenic habitat changes within forests [63], although they seem to respond negatively to habitat fragmentation per se, probably due to a limited potential to connect between fragmented forest patches across open space [37]. Further studies are urgently needed to evaluate the critical features of landscapes that are needed to sustain viable populations of this vulnerable lemur species.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A high ecological flexibility of this lemur species towards variable ecological conditions at forest edges may explain such seemingly contradictory responses, and also its occurrence in several different types of microhabitats [36]. Such a flexibility may enable this species to cope with disturbances and some anthropogenic habitat changes within forests [63], although they seem to respond negatively to habitat fragmentation per se, probably due to a limited potential to connect between fragmented forest patches across open space [37]. Further studies are urgently needed to evaluate the critical features of landscapes that are needed to sustain viable populations of this vulnerable lemur species.…”
Section: Resultsmentioning
confidence: 99%
“…M. ravelobensis forms mixed-sex sleeping groups and sleeps in tree-holes but also in dense tangles of lianas, leaves or self-built nests [38,39]. Previous studies reported certain microhabitat preferences of this species, such as habitats containing higher density of trees with many lianas and a higher cover of the herb layer, and habitats closer to surface water or at lower altitudes [36,37,40,41]. Most recently, significant regional differences were revealed in the abundance of M. ravelobensis across its distribution [37].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Mouse lemurs comprise a radiation of morphologically cryptic primates distributed throughout Madagascar (Hotaling et al, 2016). Numerous studies have suggested that their rapid speciation dynamics may reflect climatic change through time in Madagascar (Andriatsitohaina et al, 2020;Setash et al, 2017) and that their unique life history characteristics make them an ideal genetic model organism (Ezran et al, 2017;Hozer et al, 2019). Thus, an accurate mutation rate estimate for these organisms can potentially yield valuable insight into both geological and biological phenomena.…”
Section: Introductionmentioning
confidence: 99%